USEFULNESS OF FASCIA ILIACA COMPARTMENT BLOCK WITH INJECTION BUPIVACAINE AND DEXAMETHASONE AS ADJUVANT IN PATIENTS UNDERGOING HIP FRACTURE SURGERIES UNDER SPINAL ANESTHESIA - N Lil, Chaitalee; R Gajjar, Hina; Shah, Ayush; Shah, Akash; Ramani, Yagnik; Patel, Ishani (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of our study are to study the effectiveness of fascia iliaca block for positioning during spinal anesthesia and to compare the duration of post-operative analgesia using bupivacaine alone and bupivacaine with dexamethasone as an adjuvant. Methods: This was a prospective randomized study done at a general hospital. Fifty patients aged 18 years and above of ASA Grades II and III undergoing hip fracture surgeries (proximal femur nailing, DHS, and hemiarthroplasty) were included in the study to receive the fascia iliaca compartment block (FICB). Group A (25 patients) received 38 mL of 0.25% bupivacaine with 2 mL normal saline and Group B (25 patients) received 38 mL of 0.25% bupivacaine with 2ml dexamethasone (8 mg). Relief of pain for positioning during spinal anesthesia was assessed by recording the visual analog score, 30 min after the FICB. In both groups, the post-operative analgesia was recorded from the time of giving spinal anesthesia to the time for first rescue analgesia which was given when VAS was 4 or more. Results: There was a significant prolongation in the post-operative analgesia in Group B patients who received FICB with bupivacaine and dexamethasone in comparison to Group A in which bupivacaine alone was used. However, the VAS score after 30 min of FICB, for positioning for spinal anesthesia and the patient satisfaction score was similar in both groups. Conclusion: FICB is effective for providing adequate positioning for spinal anesthesia and the addition of dexamethasone (8 mg) to bupivacaine for FICB significantly prolonged the duration of the block and increased the time to first rescue analgesia as compared to using bupivacaine alone.